2007
DOI: 10.1109/iembs.2007.4353766
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Spontaneous MEG Activity in Patients with Alzheimer's Disease using Spectral Entropies

Abstract: Abstract-The aim of this study was to explore the ability of several spectral entropies to discriminate between spontaneous magnetoencephalographic (MEG) oscillations from 20 Alzheimer's disease (AD) patients and 21 controls. Hence, the relative spectral power (RSP) in classical frequency bands was calculated from the averaged power spectral density. Given the fact that the RSP can be viewed as a probability distribution function, the Shannon spectral entropy, Tsallis spectral entropy, generalized escort-Tsall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
(46 reference statements)
1
14
0
1
Order By: Relevance
“…Previous work in Alzheimer’s disease models and patients has demonstrated reductions in relative spectral power in high beta-gamma bands ( Poza et al , 2007 ), despite methodological differences between electrophysiological studies ( Dauwels et al , 2010 ). For example, in a network analysis using EEG, Petersen et al (2001) found small-worldness of networks in the gamma band correlated with cognitive performance in prodromal Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work in Alzheimer’s disease models and patients has demonstrated reductions in relative spectral power in high beta-gamma bands ( Poza et al , 2007 ), despite methodological differences between electrophysiological studies ( Dauwels et al , 2010 ). For example, in a network analysis using EEG, Petersen et al (2001) found small-worldness of networks in the gamma band correlated with cognitive performance in prodromal Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…This work has been developed on the basis of the results obtained in a pilot study where we tested several entropies using the averaged relative power over all sensors as a probability distribution. 30 Our findings suggested both a slowing of MEG rhythms and a loss of irregularity in AD. Further work should be developed to obtain a temporal evolution of the quantifiers, to assess the influence of the entropic index and to perform a spatial analysis.…”
Section: Introductionmentioning
confidence: 89%
“…Similar measures have been previously constructed to characterize Alzheimer’s disease [58], [61] and depression [60] and, in the former, were correlated with clinical measures that characterize the severity of dementia. In epilepsy, an epileptogenicity index has been defined to quantify the degree of epileptogenicity using high frequency (rapid discharges) recorded with depth electrodes [62].…”
Section: Methodsmentioning
confidence: 99%